ANALYSIS OF THE USE OF INTERFACING TYPES ON THE QUALITY OF VESTS - Chairunnisa, Putri Rahma Amalya; Asiatun, Kapti (Universitas Negeri Yogyakarta, 2024)
This research aimed to determine the characteristics of cufner, mori gula, and tricot as interfacing on semi-silk material of Corak Insang Pontianak fabric, the quality of vest products used semi-silk material of Corak Insang Pontianak fabric with cufner, mori gula, and tricot. The type of research was descriptive exploratory with a survey approach. The subject of this research was a vest design using semi-silk materials of Corak Insang Pontianak fabric with three types of interfacing. The study was repeated three times tests. Data collection used observation sheets by expert and trained panelists. Aiken's V values were 0.94, and Cronbach's Alpha was 0.762, meaning the instrument was valid and reliable. Quality indicators were measured from surface flatness, adhesion strength, surface texture, material fall, and total look. The results of the quantitative data were analyzed using a descriptive test. The results showed that the characteristics of cufner as interfacing on semi-silk material of Corak Insang Pontianak fabric was more appropriate to be used on vest, because it could support product quality standards very well compared to mori gula and tricot; The quality of vest products used semi-silk material of Corak Insang Pontianak fabric with cufner got a percentage value of 88% with an excellent category, mori gula 70% with a suitable category, and tricot 78% with a good category. It could be concluded that interfacing gave the best results based on the indicators of product quality assessment of vests using semi-silk materials compared to tricot and mori gula.